La Gestión del aprendizaje en el aula y su influencia en el rendimiento académico en el área de la matemática de los estudiantes del primer año de bachillerato general unificado de la sección vespertina del colegio de bachillerato 27 de Febrero de la ciudad de Loja, periodo 2016-2017. Lineamientos alternativos - Poma González, Vìctor Baudilio (2017)
The present investigation called THE MANAGEMENT OF LEARNING IN THE CLASSROOM AND THEIR INFLUENCE ON ACADEMIC PERFORMANCE IN THE AREA OF MATHEMATICS OF STUDENTS IN THE FIRST YEAR OF SECONDARY SCHOOL GENERAL UNIFIED OF THE EVENING SECTION OF THE COLLEGE OF HIGH SCHOOL ON FEBRUARY 27 IN THE CITY OF LOJA. Period 2016-2017, seeks to contribute to the improvement of the quality of education, for which it poses as a general objective: to determine the management of learning in the classroom and their influence in the area of mathematics of students of first year of High School General Unified of the evening section of the College of High School on February 27 of the city of Loja; research responds to a descriptive design explanatory; the phases that were used were: Comprehensive, this phase consists in the analysis, synthesis and interpretation of the management of the learning in the classroom in the course of mathematics in the first year of Secondary School General Unified; diagnosis of programming the same as was done with the survey Structured for students and teachers; the methods used were: the scientific method This method allowed to work in a systematic manner with regard to the collection, organization, analysis, and interpretation of data; the deductive method once the information, this made it possible to identify the status of the management of the learning in the classroom in the course of mathematics; analytical method helped to meet the management of classroom learning and its relationship with the academic performance of the students; inductive method facilitated the approach of the proposal that will help to improve the management of the learning in the classroom; the main results were: the lack of use of learning resources, lack of use of teaching strategies, an environment Inadequate communication, which does not allow the young men and women of the first year of Secondary School General Unified achieve meaningful learning and improve their academic performance